Role of bone scan in newly diagnosed breast cancer patients in Erbil City - Abdi, Aza Ismail; Asaad, Yassin Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
Background and objectives: It is necessary to highlight the importance of general nuclear medicine in the care of women with breast cancer including detection, classification and treatment guidance, accordingly this study was conducted to investigate the role of bone scan among newly diagnosed breast cancer patients and to find out the relationship between some clinico-pathological variables and bone metastasis. Methodology: This retrospective study was done in Nuclear Medicine unit- the radiological department of Hawler teaching hospital in Erbil City in which 40 confirmed breast cancer cases referred from various hospitals in Erbil were included in the study. Statistical Package for Social Science was used for the purpose of data analysis. Results: The age of breast cancer patients ranged from 26 to 59 years, with a mean age ± SD of 44.8 ±8.88 years. The majority (90%) were clinically presented with signs of a lump in the breasts. 62.5% of them had lymph node involvement, and the majority (95.0%) showed ductal carcinoma. Abnormal bone scan findings were identified among 42.5% of them, especially among those with stage II, advanced age, more lymph node involvement, and a sensitivity of 47.0%, and specificity of 60.9%. Multiple skeletal metastases were found most commonly in the ribs and lower limbs (67.0% and 64%, respectively).Most of the socio-demographic and clinical factors revealed non-definitive associations with the bone scan findings. Conclusions: The quality of the imaging findings was not encouraging, because of relatively low sensitivity and specificity, accordingly for each patient; the right investigative technique should be selected individually, taking into consideration different clinico-pathological features of the patients.